2020
DOI: 10.1177/2192568220942217
|View full text |Cite
|
Sign up to set email alerts
|

Structural Allograft Versus Synthetic Interbody Cage for Anterior Cervical Discectomy and Fusion: A Comparison of 1-Year Outcomes From a National Database

Abstract: Study Design: Observational cohort study. Objective: To compare 1-year perioperative complications between structural allograft (SA) and synthetic cage (SC) for anterior cervical discectomy and fusion (ACDF) using a national database. Methods: The TriNetX Research Network was retrospectively queried. Patients undergoing initial single or multilevel ACDF surgery between October 1, 2015 and April 30, 2019 were propensity score matched based on age and comorbidities. The rates of 1-year revision ACDF surgery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Most participating institutions provide data dating back to the last seven years. TriNetX has been previously used in other orthopaedic studies [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most participating institutions provide data dating back to the last seven years. TriNetX has been previously used in other orthopaedic studies [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although more than one study suggested a higher revision rate for SC, our assumptions were based on Marrache and colleagues, which compared all-cause, two-year reoperation rates after ACDF between Allo (8% in 11,514 patients) and SC (9.1% in 15,240 patients). 13,15 The second study by Veeravagu et al 14 provided probability estimates for dysphagia (4.1%) in 30,600 patients undergoing ACDF, which was presumed to be similar between the two groups. Probability estimates for the various complications other than reoperation were considered to be similar between the Allo and SC groups (Table 1).…”
Section: Probability Estimatesmentioning
confidence: 99%
“…Previous analyses comparing Allo and SC have reached mixed conclusions regarding their cost-effectiveness 7,11,12. In recent years, several large database studies comparing outcomes between the two techniques have suggested a higher revision rate with SC and may provide estimates for an improved and updated cost-utility analysis 13–15. Thus, the aim of our current investigation is to conduct a cost-analysis comparing SC versus Allo over a five-year timeframe.…”
mentioning
confidence: 99%
“…the use of an allograft spacer in ACDF has a risk of occurring various complications including infection or immune reaction due to donor tissue as well as cage-related complications including subsidence, cage migration, breakage, and collapse. ( Woo et al, 2019 ; Menon et al, 2021 ; Yang et al, 2021 ). Several bone substitutes have been developed to overcome such limitations, including bioactive ceramics, beta-tricalcium phosphate, and hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%